Ekscerpty źródłowe do dziejów archidiecezji gnieźnieńskiej i diecezji poznańskiej w czasach nowożytnych - R. Prokop, Krzysztof (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
It is already the author’s fourth publication in the excerpta series in which he makes available to Polish historians the abundant material on Polish affairs housed in the Vatican archives. The tradition of publications of this type has a long standing in Polish historical sciences. This time the author crossed the boundary of the Vatican and consulted two important Roman institutions: Archivio di Stato di Roma and Biblioteca Nazionale Centrale di Roma. The subject matter of this part of the excerpta refers to the territory of the historical Greater Poland and the representatives of the episcopate and religious orders active there. Each of the presented persons had to be connected to the history of the archdiocese of Gniezno or the diocese of Poznań in the times of Old Poland in their extensive historical borders.